(untitled) (Journal of Creative Industry and Sustainable Culture, 2024)
Gamification involves the use of game design elements and mechanics in non-game contexts, proved to increase user engagement and enhance their learning experience. It has emerged as an effective approach to promote engagement and motivation in various fields including education. Recently, the english language examination format for Sijil Peperiksaan Malaysia (SPM) and Pentaksiran Tingkatan Tiga (PT3) that examined on four skills which includes speaking, listening, reading and writing is considered tougher than previous format and it gives a significant impact and challenges towards the english language learning approach. The traditional teaching method has been adapted and aligned with Common European Framework Reference (CEFR). However, the effectiveness of formal teaching approach is arguable. The main aim of this study is to develop an Ace English, a prototype of a gamified English learning mobile application (app) using ADDIE model. An expert review also has been conducted as an evaluation method in evaluating the mobile app. The evaluation was conducted with five experts to evaluate the Ace English in essential dimension which are content, design and function. Findings has shown that all the experts have positive experience on all the three dimensions. Suggestion for improvement and amendments have been made for the definitive better version of Ace English.